Relationship Pattern Fishing With Eating Stunting Events In Children - Tenriwati; Marwidah; Khaerunnisa (Lembaga Penelitian dan Pengabdian Masyarakat, Stikes Panrita Husada Bulukumba, 2019)
In 2016 according to WHO more than25 ℅ the number of children under the age of five years was around 166 million children who experienced stunting, whereas in 2018 the prevalence of stunting in South Sulawesi decreased by around 30.8 ℅, but if the stunting problem was still above 20 ℅, then it is still a public health problem. The research purposes to know relationship parenting feeding with an incident of stunting on toddlers. This research is quantitative research through observational analytic approaches with cross-sectional design. The number of samples was 36 people from all populations of toddlers in the working area of the gattareng health center with a sampling technique using consecutive sampling. Data processing using the chi-square test with the significance value a <0,05. The result of the study there is a relationship between parenting feeding and incident of stunting with value p:0,000 <0.05. Parenting feeding is in the lacking category as much as 52,8℅ and incident of stunting as much as 50,0℅.